Changing What We Tax: Free-enterprise Solutions for Energy Security and Climate Change (Part 2) - Inglis, Bob (Kansas State University, 2012)
Bob Inglis is passionate about free enterprise solving our energy and climate challenge. A former South Carolina congressman, his service on the House Foreign Affairs Committee taught him just how much our petroleum dependency threatens our national security. While serving on the House Science Committee, he learned how that threat could be multiplied if scientists are right about our changing climate. Inglis is now the executive director of the new Energy and Enterprise Initiative at George Mason University. Through this initiative, Inglis is leading national-level policy discussions about responding to climate change based on conservative policy principles.
Keywords: Energy; Climate change; Policy; Conservative principles; Free enterprise